2018
DOI: 10.1186/s40249-018-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for avian influenza virus in backyard poultry flocks and environments in Zhejiang Province, China: a cross-sectional study

Abstract: BackgroundHuman infection of avian influenza virus (AIV) remains a great concern. Although live poultry markets are believed to be associated with human infections, ever more infections have been reported in rural areas with backyard poultry, especially in the fifth epidemic of H7N9. However, limited information is available on backyard poultry infection and surrounding environmental contamination.MethodsTwo surveillance systems and a field survey were used to collect data and samples in Zhejiang Province. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Indeed, rest days/nights are an important component of long‐term AIV control but are not sufficient alone to eliminate infection (Kung et al, ). Furthermore, risk factor studies in LBMs have shown that having a greater variety of poultry species, including ducks being sold alongside other species, having poor sanitary conditions, storing poultry in floor pens instead of cages and having ≥1 wholesaler trading in LBMs, all increase the odds of having AIV‐infected poultry and/or having AIV‐contaminated environments (Kim et al, ; Kirunda et al, ; Santhia et al, ; Sayeed et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, rest days/nights are an important component of long‐term AIV control but are not sufficient alone to eliminate infection (Kung et al, ). Furthermore, risk factor studies in LBMs have shown that having a greater variety of poultry species, including ducks being sold alongside other species, having poor sanitary conditions, storing poultry in floor pens instead of cages and having ≥1 wholesaler trading in LBMs, all increase the odds of having AIV‐infected poultry and/or having AIV‐contaminated environments (Kim et al, ; Kirunda et al, ; Santhia et al, ; Sayeed et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies are also relatively weaker in establishing causality of risk factors than with an analytic design, such as with a cohort study. 61 Well-designed prospective epidemiological studies with follow-up of human and their birds will be better suited to answer such questions. 46 The authors acknowledge that including control human sera from repository of a private laboratory in Chakwal, which were not collected in the same time frame in which the butchers' sera were collected, might have introduced bias in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the current study was a cross‐sectional survey; these study designs are not suited to estimate disease incidence, natural history of disease, or the rate of secondary human‐to‐human infection. Cross‐sectional studies are also relatively weaker in establishing causality of risk factors than with an analytic design, such as with a cohort study . Well‐designed prospective epidemiological studies with follow‐up of human and their birds will be better suited to answer such questions .…”
Section: Discussionmentioning
confidence: 99%
“…Among these viruses, H5N6 HPAIVs has crossed the species barrier and caused human infection cases, posing a new threat to public health in China. Notably, among these human infection cases, most of the patients have had a contact history with the infected poultry in live poultry markets (LPMs) or backyard poultry flocks (BPFs), which are considered the major risk factors in human infection cases [24,25]. Recent epidemiological study demonstrated that H5N6 HPAIVs have replaced H5N1 HPAIVs as the dominant subtype in waterfowls in Southern China.…”
Section: Discussionmentioning
confidence: 99%